Aplikasi Petrinet Pada Sistem Antrian Servis Produk Barang - Afif, Ahmad (Mathematics Department, Faculty of Mathematics and Sciences Unisda Lamongan, 2024)
Queueing systems are a critical element in the operational management of service processes for goods, such as repairs, warranty claims, or product replacements. Efficient queue management can enhance productivity, reduce customer waiting times, and provide a better service experience. This study aims to apply petri nets to model the queueing system for product service processes. The resulting model, comprising five places and six transitions, was evaluated through simulation using the PIPE software and further analyzed with max-plus algebra. This analysis produced matrix equations capable of estimating service times and the duration of the queueing process until completion, thereby expected to improve the efficiency and quality of service in the queueing system.